Effects of a Teacher‐Designed and Teacher‐Led Numerical Board Game Intervention: A Randomized Controlled Study with 4‐ to 6‐Year‐Olds. Issue 1 (20th August 2019) - Hawes, Zachary; Cain, Michelle; Jones, Shelly; Thomson, Nicole; Bailey, Cristol; Seo, Jisoo; Caswell, Beverly; Moss, Joan
ABSTRACT: The purpose of the current pilot study was to examine the effects of a teacher‐designed and teacher‐led numerical board game intervention. Fifty‐four 4‐ to 6‐year‐olds were randomly assigned to either the number board game intervention or an active control group. Relative to the control group, children who received the number game intervention demonstrated significant improvements on a numeral identification task. This finding is significant in so far as numeral identification skills play a critical role in more advanced numerical and mathematical reasoning. There was no evidence of training‐related improvements on any of the other tasks. In addition to the intervention effects, the present study provides an example of a successful teacher‐researcher collaboration, providing new insights into the making of bidirectional relations between research and practice.